2022
DOI: 10.1101/2022.05.16.492060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrastructure Expansion Microscopy reveals the nanoscale cellular architecture of budding and fission yeast

Abstract: The budding yeast Saccharomyces cerevisiae and the fission yeast Schizosaccharomyces pombe have served as invaluable model organisms to study various fundamental and highly conserved cellular processes. While super-resolution (SR) microscopy has in recent years paved the way to a better understanding of the spatial organization of molecules in cells, its wide use in yeast models has remained limited due to the specific know-how and specialized instrumentation required, contrasted with the relative ease of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(98 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, cells lacking the mitochondria-MT linker protein Mmb1 do not associate with MTs (15). We confirmed these observations by visualising MTs and mitochondria in ultrastructure-expanded images (17) of WT, Dnm1Δ and Mmb1Δ cells (1A, Video S2), and indeed quantified higher rates of attachment of mitochondria to MTs in Dnm1Δ cells compared to WT cells (1B). In our previous work, we showed that this dissociation of mitochondria from MTs results in fragmentation of the mitochondrial network (Fig.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…On the other hand, cells lacking the mitochondria-MT linker protein Mmb1 do not associate with MTs (15). We confirmed these observations by visualising MTs and mitochondria in ultrastructure-expanded images (17) of WT, Dnm1Δ and Mmb1Δ cells (1A, Video S2), and indeed quantified higher rates of attachment of mitochondria to MTs in Dnm1Δ cells compared to WT cells (1B). In our previous work, we showed that this dissociation of mitochondria from MTs results in fragmentation of the mitochondrial network (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Ultrastructure expansion microscopy was performed as described in (17), with some modification to the cell fixation. Briefly, cells were grown in YES at 32°C for 36 h, followed by high pressure freezing.…”
Section: Methodsmentioning
confidence: 99%
“…Assembly of the second array of Sfi1/Cdc31, anti‐parallel to the first and associated with it through Sfi1 C‐termini, provides the site for daughter SPB assembly, thereby controlling conservative SPB duplication (Kilmartin, 2014; Bouhlel et al , 2015; Bestul et al , 2017; Rüthnick et al , 2021). Recently, applying U‐ExM to budding yeast allowed the visualization of the Sfi1/Cdc31 core module on the half‐bridge structure (preprint: Hinterndorfer et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to electron microscopy (EM), subcellular compartments can now be imaged in their entirety, without the need for specific labels and with a lateral spatial resolution of ~15 nm. Our pan-staining concept has been since adapted by many labs to examine contextual spatial information in a multitude of biological systems, and at different expansion levels, demonstrating the wide utility of this contrasting approach (Nijenhuis et al, 2021;Sim et al, 2021;Klimas et al, 2021;Damstra et al, 2022;Laporte et al, 2022;Shaib et al, 2022;Hinterndorfer et al, 2022;Rashpa and Brochet, 2022;Pacheco et al, 2021;Suen et al 2022).…”
Section: Mainmentioning
confidence: 99%